2013
DOI: 10.1186/1471-2156-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and gene expression QTL mapping in mice reveals imprinting and interaction effects

Abstract: BackgroundShifts in body composition, such as accumulation of body fat, can be a symptom of many chronic human diseases; hence, efforts have been made to investigate the genetic mechanisms that underlie body composition. For example, a few quantitative trait loci (QTL) have been discovered using genome-wide association studies, which will eventually lead to the discovery of causal mutations that are associated with tissue traits. Although some body composition QTL have been identified in mice, limited research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In this study, the trait with the greatest proportion of phenotypic variance explained by imprinting effects was backfat (0.017 in the Landrace, 0.029 in the Large White, and 0.020 in the Pietrain population), although the estimates were still quite low, in comparison with the amount of narrow-sense heritability and the proportion of phenotypic variance explained by dominance effects. In mice, a gene expression QTL mapping study for body composition traits showed that imprinting QTL accounted for only a limited amount of the phenotypic variance (<2.50%) for most traits ( Cheng et al 2013 ). In a pedigree-based study in pigs, it was shown that 5–7% of the phenotypic variance of backfat and 1–4% of growth rate was explained by paternal imprinting ( De Vries et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the trait with the greatest proportion of phenotypic variance explained by imprinting effects was backfat (0.017 in the Landrace, 0.029 in the Large White, and 0.020 in the Pietrain population), although the estimates were still quite low, in comparison with the amount of narrow-sense heritability and the proportion of phenotypic variance explained by dominance effects. In mice, a gene expression QTL mapping study for body composition traits showed that imprinting QTL accounted for only a limited amount of the phenotypic variance (<2.50%) for most traits ( Cheng et al 2013 ). In a pedigree-based study in pigs, it was shown that 5–7% of the phenotypic variance of backfat and 1–4% of growth rate was explained by paternal imprinting ( De Vries et al 1994 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the estimation of heritability via the use of additive models does not only capture additive gene action but can potentially also capture part of the dominance effects and epistatic interactions ( Hill et al 2008 ; Falconer and Mackay 1996 ). In addition, traditional additive models ignore imprinting effects, which also are expected to contribute to the genetic architecture and evolution of complex traits ( Lawson et al 2013 ; Cheng et al 2013 ). Therefore, the proportion of phenotypic variation that is explained by all genetic effects and how much of the total genetic variation is actually due to additive effects is still unclear in modern genetics ( Vinkhuyzen et al 2013 ).…”
mentioning
confidence: 99%
“…In harmony with the difference between Compact mice and myostatin-null mice, the spectra of modifier loci identified in myostatin-null mice [33,34] are markedly different from those defined using Compact mice [12,13,25,26]: in the case of myostatin-null mice twelve Quantitative Trait Loci were identified on mouse chromosomes 1,3, 6, 7 that significantly interacted with the myostatin genotype [34], whereas in the case of compact mice hypermuscularity was associated with several unrelated markers, markers on chromosomes 16 and X showing the strongest association [12,13]. 0.85 GMQE score*: 0.55 *GMQE scores (Global Model Quality Estimation score, ranging between 0-1) combine properties from the target-template alignment and reflect the expected accuracy of a model built with that alignment and template.…”
Section: Resultsmentioning
confidence: 96%
“…The identification of Atp2a2 (a.k.a. Serca2a ) as the top-ranked RIF2 gene at d35 is particularly noteworthy, because it was previously identified as a potential modifier of MSTN in a large F2 mouse study [ 47 ]. The ATP2A2 calcium pump affects sarcoplasmic reticulum function and muscle fiber type.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP2A2 calcium pump affects sarcoplasmic reticulum function and muscle fiber type. Transgenic Atp2a2 mice exhibit cardiac hypertrophy [ 47 50 ]. Furthermore, pharmacological inhibition of SMAD2 in cardiomyocytes indicates that TGFβ/SMAD2 signaling regulates ATP2A2 function [ 51 ].…”
Section: Discussionmentioning
confidence: 99%